Phenolic compounds from Chaenomeles speciosa alleviate inflammation in lipopolysaccharide-treated RAW264.7 macrophages via the NF-κB and MAPK pathways - Fuxia Hu; Chao Liu; Fengqin Wang; Changxin Zhou; Maotong Zhu; Dongxiao Sun-Waterhouse; Zhaosheng Wang (Food Science and Human Wellness)
Chaenomeles speciosa (Sweet) Nakai cultivated widely in temperate regions possesses anti-inflammatory properties, however, the underlying molecular mechanisms remain not fully understood. In this study, a purified phenolic extract of C. speciosa rich in chlorogenic acid, procyanidin B1 and catechin (determined by HPLC-Q-TOF-MS/MS) exhibited dose-dependent anti-inflammatory effects on lipopolysaccharide (LPS)-treated RAW264.7 macrophages. The extract at 30 μg/mL was most potent and enabled most cells in normal morphology under LPS stimulation without causing cytotoxicity. The extract suppressed the levels of nitric oxide (NO), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and interleukin-1β (IL-1β), and the mRNA and protein expressions of nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2). The mechanisms underlying such anti-inflammatory actions included the regulation of phosphorylation of related proteins to monitor the expressions of inflammatory mediators and genes in the nuclear factor kappa-B (NF-κB) and mitogen-activated protein kinase (MAPK) signaling pathways. Therefore, the phenolic extract from C. speciosa is a desirable anti-inflammatory agent for inflammatory conditions to meet the rising demand for natural and cost-effective therapeutics.